(untitled) (Journal of Computational Mathematics, 2006)
Some quadrature methods for integration of _a^b f(x)e^i ω g(x)dx for rapidly oscillatory functions are presented. These methods, based on the lower order remainders of Taylor expansion and followed the thoughts of Stetter [9], Iserles and Nørsett [5], are suitable for all ω and the decay of the error can be increased arbitrarily in case that g'(x) ot=0 for x[a,b], and easy to be implemented and extended to the improper integration and the general case I[f]=_a^b f(x)e^ig(ω,x) dx.